Evaluation of Online Psychological Assessment in Mental Health Services: User Perspectives and Implications for Counseling Practice - Devy Sekar Ayu Ningrum; Sitti Rahma Zuleykha Aven Hinelo; Nazwa Rizkia Ismail; Husnul Marhamah Ifka; Indah Khairunnisa Pakaya (International Journal of Counseling and Psychotherapy, 2026)
Background: The rapid acceleration of digitalization has expanded the accessibility of contemporary mental health services; however, transitioning clinical assessments to virtual settings raises concerns regarding diagnostic accuracy due to the limited observation of clients' nonverbal behaviors. Objective: This study aimed to evaluate the effectiveness, strengths, and limitations of online psychological assessment from the perspective of university students. Methods: A descriptive qualitative design was employed. Data were collected through in-depth interviews with undergraduate students at Universitas Negeri Gorontalo who had experienced telemental health services, and were analyzed using thematic analysis. Results: Online psychological assessment is highly effective for early detection, rapid preliminary screening, and mitigating social stigma by providing anonymity that fosters client self-disclosure. However, its diagnostic efficacy is fundamentally constrained by systemic losses of nonverbal cues (such as micro-expressions and body language) and technical signal latencies. Conclusion: Virtual psychological assessment cannot entirely replace traditional face-to-face clinical evaluations but functions as a vital, complementary entry point within a hybrid telemental health counseling model. This approach integrates the accessibility and stigma-reducing benefits of digital platforms for initial screening with the diagnostic depth of in-person clinical observation. Originality/Value: This study offers novel empirical insights into the field of clinical psychology and telemental health by uncovering qualitative evaluations of virtual psychological assessments within a regional higher education context that has remained underexplored. These findings enrich empirical evidence while providing a strategic reference for university counselors and mental health practitioners in formulating and developing standardized virtual assessment protocols.